Clinician Perspectives on Barriers to Advance Care Planning Among Vulnerable Patients. (20th August 2020) - Ashana, D.; Reich, A.; Gupta, A.; Perez, S.; D'Arcangelo, N.; Gazarian, P.; Tjia, J.; Halpern, S.; Weissman, J.; Ladin, K.
Abstract : Research Objective: Vulnerable patients, such as racial and ethnic minorities, infrequently participate in advance care planning (ACP). Reasons underlying low uptake are not well understood. We sought to examine clinician perspectives regarding barriers to ACP among vulnerable populations. Study Design: Case studies with semi‐structured interviews. Population Studied: Health systems were purposively selected by an expert advisory panel to ensure diversity of health system size, region, type (ie, academic, public, nonprofit), and religious affiliation. Within each site, a purposive sample of 10–13 clinicians was selected by the chief medical officer or a palliative care leader based on clinician role (eg, physicians, nurse practitioners, social workers), specialty, and experience with ACP. Principal Findings: We interviewed 75 clinicians at 6 health systems after which we reached thematic saturation. When asked to describe characteristics of patients with whom they have difficulty discussing ACP, clinicians most frequently identified racial and ethnic minorities and non‐English or non‐native English speakers. Four themes emerged that characterized clinicians' perspectives regarding barriers to ACP among vulnerable patients. First, clinicians had preconceived notions that vulnerable patients were reluctant to participate in ACP due to mistrust of the health care system or cultural beliefs that preclude discussions about death and dying. Second, these preconceptions led to clinicians feeling anxious while discussing ACP with vulnerable patients, resulting in their avoiding ACP altogether or undertaking only cursory explorations of these patients' goals and values. Third, clinicians had fixed beliefs about successful ACP (eg, identifying a single decision maker, completing legal documents) that were often discordant with preferences among vulnerable patients. Fourth, clinicians reported insufficient institutional resources to properly engage vulnerable patients, including in‐person translators with training in discussing ACP. Conclusions: We identified several clinician‐ and institution‐level factors that may mediate low uptake of ACP among vulnerable patients, suggesting that observed differences in rates of ACP between vulnerable patients and others may be modifiable. Implications for Policy or Practice: Current efforts to promote ACP, including Medicare's ACP billing codes, may not be effective in all patient populations due to clinician‐ and institution‐level barriers to ACP that are unlikely to be addressed by financial incentives. Additional research is needed to more completely characterize clinician decision making regarding ACP among vulnerable patients, including developing interventions to modify heuristics that may lead to disparities with a goal of ensuring equitable access to ACP among all patients. Institutions should also consider investing in more robust translator programs to facilitate ACP discussions with non‐English and non‐native English speakers. Primary Funding Source: National Institutes of Health.